Kandinsky and Bergson: Between form and Sense. A Phenomenological view (Itinera, 2024)
The mode of evolution from figurative to abstract and from abstract to concrete in Kandinsky’s work seems to follow the path of a Bersonianan creative evolution. From the first melodic paintings to the explosion of his improvisations, the aesthetic material contracts and condenses itself in a pure shape with no connections with the representativeness. This eidetic shape is also the result of a phenomenological approach and analysis, revealing correlating meanings in an interesting living time of perception. Oscillations between shape and content, color and sound in resonance space will become for Kandisnky scope for the constitution of a possible aesthetic phenomenological experience, that looks for unveiled qualities. For Kandinsky and Bergson the quality in which an element contracts or thickens itself is in fact a new spiritualized value.Kandinsky looks for a real intense time of perception, of creation, of fruition that finds in the real movement and the Bergsonian durée réelle his theoretical confirmation. At the same time his creative act seems to be able to fit into the dual modality of Bergsonianan life of consciusness: frist like an élan vital and explosive action of abstract expressionism and subsequently as a work of qualitative contraction and condensation of vibrations that create a new kind of material. Tensions for the philosopher and the painter are the material established to ensure continuity between real and ideal. The experience in the field of sensibility for Kandinsky follows the paths of intuition and intelligence in the dual Bergsonian modality of a double vital and evolutionary movement : listening the melodic curvature of soul that exposes and explodes sense and forms and  contracting itself in a rhythmic tension of Bergsonianan durée, so that tension will be an orchestral partiture where the flow could be read. The aesthetic object presents itself as a movement towards the fullness of a eidetic unity, paying attention to its morphogenetic movement towards the possibility to take shape of that movement.In fact, the artist’s gaze is a grasp on the movements of being, it is a gaze that doesn’t leave the movement of Sense, and like music tends to guarantee its continuity, The flow that he follows is the flow of music that he tries to become more and more concrete. The form of the Sense is instead correlation of contracted quality understood as expressive density, like a quantum. Sense and form objectify themself to create abstract art. Shape that can condense a flow of a special time of consciousness letting move its inner sound and contracting and diluting itself in a vectorial sense that can orchestrate forms and write scores. Sense insinuates itself into material and the same material reveals, redefines, redirects. The Sense of the form is pure quality in progression, vibranting eternity in the first expressionism period, and expressive density in the following Bauhaus period until it becomes an organic complete unveiling resonant shape. Unveiling qualities flow as a bridge between spirit and material, speaking about a deep interesting space-time that suggests a hidden and special physics of soul. The bridge that can reveal and connects possible inner worlds is a space-time experience of a living inner time of perception that make sense in the music. Space and time vibrate and grow in rhythmic resonance until becoming an organon, a pure body. Space time will become correlation and redefinition scope of essence, form and soul.
Keywords: Space-time, Sense, Durée réelle, Phenomenology